Interactive Ethnoscience Based E-Modules for Optimizing Science Learning in Indonesia: A Systematic Literature Review - Maria, Enni; Rosa, Friska Octavia; Pratiwi, Dasrieny; Suseno, Nyoto (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to review the literature related to the integration of ethnoscience in interactive e-modules for science learning and evaluate its impact on the understanding of science concepts, motivation, and student involvement. The method used is Systematic Literature Review (SLR) with the PRISMA approach, which involves searching and selecting articles from various academic databases. A total of 10 relevant articles published between 2024 and 2025 were included in the analysis. The results of the literature review show that the integration of ethnoscience in interactive e-modules significantly improves students' understanding of science concepts in a way that is more contextual and relevant to the local culture. The use of ethnoscience-based e-modules has also been shown to increase student motivation and engagement in learning, by connecting science with daily life and local culture. The implications of these findings are the importance of developing e-modules that are more inclusive and adaptive to cultural diversity, as well as increasing access to technology throughout Indonesia to ensure wider and more equitable implementation.